Optimal design of composite structures : a historical review - Ganguli, Ranjan (2015)
Composites are widely used in aerospace structures; however, most designs do not exploit the inherent tailorability of composites. Optimization methods can be used to design composite structures by tailoring the ply angles and stacking sequences. Typical objectives include minimum weight and constraints include strength, buckling, displacements and frequencies. This paper covers some of the literature in the area, with the objective of understanding the historical evolution of the field. Some ideas for future research are provided. It is hoped that the review will provide new researchers with a basic idea about the growth of the field and point them towards useful references for further information.